Study of the Concentration of Some Pollutants in reject brine from Water Purification Plants in Tajoura, Libya - Nader Abdulhamid Elaziby; Wafa Khalleefah Amhimmid; Souad Mohamed Kshed; Hanan A. Mosbah (African Journal of Advanced Pure and Applied Sciences, 2025)
The study was conducted in Tajoura (21 km east of Tripoli) from the end of December 2022. Fourteen samples were collected from various stations in the study area. After conducting the necessary analyses and comparing the results with international standards, it was discovered that most of the stations examined exceeded the permitted limits for treated wastewater. The total dissolved salts in the wastewater ranged between 286.3 and 11,286.7 mg/L, while the concentration in the well water varied from 70 to 6,545 mg/L. Additionally, chloride concentrations in the water were found to be as high as 6,742.6 mg/L, with a sodium concentration of 1,719.0 mg/L. These results clearly show that wastewater from water purification plants is a significant source of environmental pollution due to its high pollutant concentration. Therefore, it is crucial for the relevant authorities to monitor the stations and require the implementation of treatment units to process the wastewater generated by these plants before it is released into the environment. This is important because the damage caused by these pollutants to the environment highlights the need to consider the environmental aspect when establishing water purification plants. Consequently, environmental impact assessments should be conducted during the planning process, appropriate technologies should be selected, and environmentally friendly materials should be utilized in the operation of these stations.